Persistent metallic Sn-doped In2O3 epitaxial ultrathin films with enhanced infrared transmittance - Dongha Kim; Shinbuhm Lee (Scientific Reports, 2020)
Abstract Infrared transparent electrodes (IR-TEs) have recently attracted much attention for industrial and military applications. The simplest method to obtain high IR transmittance is to reduce the electrode film thickness. However, for films several tens of nanometres thick, this approach unintentionally suppresses conduction due to surface electron scattering. Here, we demonstrate low sheet resistance (<400 Ω □−1 at room temperature) and high IR transmittance (>65% at the 2.5-μm wavelength) in Sn-doped In2O3 (ITO) epitaxial films for the thickness range of 17−80 nm. A combination of X-ray spectroscopy and ellipsometry measurements reveals a persistent electronic bandstructure in the 8-nm-thick film compared to much thicker films. This indicates that the metallicity of the film is preserved, despite the ultrathin film configuration. The high carrier mobility in the ITO epitaxial films further confirms the film’s metallicity as a result of the improved crystallinity of the film and the resulting reduction in the scattering defect concentration. Thus, ITO shows great potential for IR-TE applications of transparent photovoltaic and optoelectronic devices.